Pollution and its Impacts in Ennore Creek, Southeast Coast, India – A Review - Lakshmi, V. V.; Ruby, P.; Jayakumar, N. (International Journal of Bio-resource and Stress Management, 2024)
The coastal ecosystem is essential to life on our planet as well as to the support of the livelihood of people living near and dependent on the coastal resources. The abundance of coastal resources of good quality is fundamental to all marine biological processes, for maintenance of biodiversity and ecosystems and for primary and secondary production functions that support human needs. Coastal ecosystems are ecologically important on the global scale and highly valuable for the services they supply. These include regulation services such as shoreline stabilization, nutrient regulation, carbon sequestration, and both detoxification of polluted waters and waste disposal; provisioning services such as supplying food, fuelwood, energy resources, and natural products; and amenity services such as coastal livelihoods, shipping, domestic tourism and recreation, and international tourism and recreation. In the seas, the marine life faces threats in many ways, such as overexploitation and harvesting, deposit of waste, contamination, exotic species, soil recovery, dredging and global climate change. One of the major kinds of human impact constitutes a major threat to marine life: the pollution by plastic debris. Most of the world’s important fisheries have now been damaged to varying extent; situations are even more critical in those fisheries that are already overexploited or otherwise vulnerable and, therefore, deserve immediate attention. Effective and sustainable management of coastal and marine environment should be initiated from local to international and global scale to ensure a sustained and best possible utilization of the resources for broader interest of mankind.